300 FROM OVER 40 COUNTRIES GATHER IN PENANG FOR MOLLUSC CONGRESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 July 2016 – An international congress will gather some 300 scientists, researchers, government administrators, students and industrial partners from more than 40 countries to deliberate on issues pertaining to molluscan (animals with shells including snails, clams, octopuses and squids) studies.